Nineteenth-century design.
1 online resource (xi, 451 pages)
Keywords: This is volumefour in a four-volume edition of primary source materials that document the histories of design across the long nineteenth century. Each volume is arranged by appropriate sub-themes and it is the first set of primary sources to be gathered together in this comprehensive and accessible format. Design refers to more than simply products and personalities or even cultural ideas, it involves consideration of ways of design thinking and applications as well as the philosophies and the other disciplines that impinge upon it. Here, the final volume looks at consumption and uses of design as a part of the wider cultures of the period. The volumes will be of interest to a range of scholars and students, including those in art and design history, visual culture, and nineteenth-century material culture. They will also be of interest to a broad range of scholars working in areas including aesthetics, gender, politics and philosophy.